2004
DOI: 10.1093/jn/134.7.1690
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol Oxidation Products Are Absorbed in the Intestinal Lymphatics in Rats but Do Not Accelerate Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: Phytosterol oxidation products (oxyphytosterols) are formed during the processing and storage of foods. However, it is unknown whether oxyphytosterols affect human health. To address these issues, we prepared beta-sitosterol and campesterol oxides, evaluated their lymphatic absorption in rats, and examined the effect of an oxyphytosterol diet on atherosclerosis in apolipoprotein (apo) E-deficient mice. The lymphatic absorption of cholesterol and 6 oxyphytosterols (7alpha-hydroxy, 7beta-hydroxy, beta-epoxy, alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 46 publications
2
122
2
1
Order By: Relevance
“…As it has been reported, the absorption of campesterol (and its oxides) is higher than that of sitosterol (and its oxides) (12,66 ). Nevertheless, oxysitosterol plasma levels are usually higher than campesterols levels, probably due to in vivo oxidation of sterols (67).…”
Section: Effect Of the Type Of Sterolmentioning
confidence: 93%
See 1 more Smart Citation
“…As it has been reported, the absorption of campesterol (and its oxides) is higher than that of sitosterol (and its oxides) (12,66 ). Nevertheless, oxysitosterol plasma levels are usually higher than campesterols levels, probably due to in vivo oxidation of sterols (67).…”
Section: Effect Of the Type Of Sterolmentioning
confidence: 93%
“…In this context, there is evidence that SOPs are actually absorbed from the diet (12,13). Given their potentially harmful effects on human health, a deeper study of the factors affecting the formation of dietary SOPs is essential.…”
Section: Introductionmentioning
confidence: 99%
“…1) could have toxic effects on human organisms similar to those of cholesterol oxidation products (COP) (Garcia-Cruset et al 2002). POP were shown to be accumulated in the serum and liver of mice (Tomoyori et al 2004), and to have cytotoxic effects on mammalian cells (Maguire et al 2003). POP were identified in the plasma of human subjects in amounts ranging from 4.80 to 57.2 ng/mL (Grandgirard et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…POP were identified in the plasma of human subjects in amounts ranging from 4.80 to 57.2 ng/mL (Grandgirard et al 2004). However, several aspects of the possible toxic effects of POP are still to be elucidated (Tomoyori et al 2004;Lea et al 2004). Maguire et al (2003) reported that β-sitosterol oxides exhibit less severe but similar toxicity patterns to those found for COP.…”
Section: Introductionmentioning
confidence: 99%
“…POPs have been detected to be absorbed in experiments carried out with rats [8][9][10] and they have also been found in human healthy volunteers [11,12]. The toxicological effects of COPs have been well documented because of their wide range of adverse biological effects related to citotoxicity, apoptosis, mutagenesis and carcinogenesis; being specially important the fact that the presence of COPs in human macrophages/foam cells and atherosclerotic plaques has been suggested to induce the development of atherosclerosis [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%